2020
DOI: 10.1007/s10805-019-09357-x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Discipline Integration by Contract Cheating Services and Essay Mills

Abstract: Contract cheating services are marketing to students at discipline level, using increasingly sophisticated techniques. The discipline level reach of these services has not been widely considered in the academic integrity literature. Much of the academic understanding of contract cheating is not discipline specific, but the necessary solutions to this problem may need to vary by discipline. This paper reviews current knowledge about contract cheating services at the discipline level, including summarising four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
0
15
0
3
Order By: Relevance
“…Many forms of assessment are susceptible to contract cheating. The literature in this field has revealed that an aggressive industry exists, aiming to implore students to cheat (Ellis et al 2018;Lancaster 2020a). Contract cheating solutions can be purchased cheaply by students, often from writers operating in economic surroundings where incomes are typically low (Lancaster 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Many forms of assessment are susceptible to contract cheating. The literature in this field has revealed that an aggressive industry exists, aiming to implore students to cheat (Ellis et al 2018;Lancaster 2020a). Contract cheating solutions can be purchased cheaply by students, often from writers operating in economic surroundings where incomes are typically low (Lancaster 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, law was identified as a discipline where academics are reluctant to prosecute misconduct for fear of terminating a student's progression to registration. This is of great concern, particularly in the UK, where law has been identified as particularly susceptible to essay mills (Lancaster 2020). Some academics, who may or may not have a centralized process to rely on for the investigation and management of student misconduct, choose to 'turn a blind eye' either because they feel emotionally exhausted by conflict, or because they feel their workload is already high enough without adding to it.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that contribute to misconduct have also been investigated (Barbaranelli et al 2018;Grira and Jaeck 2019;Moss et al 2018;Yu et al 2018), including cultural or international status (Ison 2018;James et al 2019;Mahmud et al 2019;Makarova 2019). While most current research in the area of student misconduct relates specifically to plagiarism, considerable work has been in respect of contract cheating (Bretag et al 2020;Dawson and Sutherland-Smith 2018;Harper et al 2019), particularly the motivation for student use (Amigud and Lancaster 2019a;Rundle et al 2019;Sarwar et al 2018), essay mill processes (Ellis et al 2018;Foltýnek and Králíková 2018;Kaktiņš 2018;Lancaster 2020;Medway et al 2018;Rowland et al 2018) and the relationship with assessment design (Bretag et al 2019b;Ellis et al 2019;Harper et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Contract cheating is not restricted to computer science; students across many disciplines in higher education engage in this practice (Harper et al, 2019). Lancaster (2020) found that students of the professional programs of architecture, computer science, and law were at the highest risk to use essay mills or companies "that provide pre-written assignments to students…commissioned on a (supposedly) bespoke basis from ghost writers" (Medway et al, 2018, p. 393). More recently, contract cheating has expanded to include online commercial businesses, which have been described as file sharing sites, and include instructors lecture notes, presentation slides, tests, assignments, research dissertations, lab reports, along with other services that students can purchase (Ellis et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%